A Study on Marginalized Women Working in the Carpet Factories in Kathmandu - Thadathil, Boby Joseph (SXC Journal, 2025)
Several marginalized women work in carpet factories in Nepal. These women are mostly unemployed and illiterate. The study aims to understand their working conditions, life situations, and the challenges that they face both at work and at home. The researcher interviewed nine such female workers in local dialects after obtaining their verbal consent in the Boudha area of Kathmandu, Nepal. These women had experienced physical, psychological, and economic stress. They came to the city for a better life, education for their children, and employment opportunities. The study shows that the workers are unsatisfied with their pay and the working environment, and struggle to live in the city. The study also found that they are vulnerable and often paid less than what is needed to meet their needs.